Acute myeloid leukemia with fusion resembling acute promyelocytic leukemia, initially presenting as sweet syndrome: A case report and literature review - Huan Liu; Guo-Xia Liu; Feng-Hai Liu; Shu-Guo Wang (Journal of International Medical Research)
Some subtypes of acute myeloid leukemia share morphologic, immunophenotypic, and clinical features of acute promyelocytic leukemia but lack a promyelocytic leukemia–retinoic acid receptor alpha fusion gene. Herein, we present a case of acute myeloid leukemia with morphological and clinical features resembling those of acute promyelocytic leukemia, carrying the rare DEK::NUP214 fusion gene and presenting with sweet syndrome as the initial manifestation. In our case, the patient with acute myeloid leukemia carrying DEK::NUP214 fusion exhibited highly active bone marrow proliferation, with increased basophil and promyelocyte counts. To the best of our knowledge, this is the first reported case of acute promyelocytic leukemia–like acute myeloid leukemia carrying DEK::NUP214 fusion.